Appreciation of contemporary batik art on shoes: The perception of primary year six student of SK Padang Jawa, Shah Alam / Mohd Noor Fazil - Fazil, Mohd Noor (2013)
The purpose of this research is to create batik pattern on shoes as the teaching aid for art education in school. This research will also investigate the primary school,Year 6 students perception.there are several new ideas and proposal made by the resercher to increase the appreciation of contemporary batik, a research has been made using the quantitative method by distributing the questionnaire which is divided into two parts. The samples for this research are constituted by 40 year 6 students primary school. The data were analyzed by looking at the frequency of each questions. Besides, the research also identify that the pupils agreed that that using batik shoes as teaching aid is safe because the ingredients and the the tools used are safe.